Hubungan Kontrol Diri dengan Pemujaan terhadap Idoal pada Penggemar K-Pop di Aplikasi X - Maudina, Marsyah Aulia; Nathania, Putri; Wulandari, Devi (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
This research aims to determine the relationship between self-control and celebrity worship in K-Pop fans on the X Application. This research uses a quantitative method. The population of this research were early adults aged 18-24 years old who are K-Pop fans on the X application. The sampling technique in this research used purposive sampling with a total sample of 635 people. The data collection method was carried out using the self-control scale from Tangney 2004 and the celebrity worship scale from Maltby 2004. The collected data were analyzed using the Pearson R correlation test, the results of this research the correlation value = (p = 0.695, p > 0.05) which indicates that there is no significant relationship between self-control and celebrity worship in K-pop fans.